2018
DOI: 10.3390/ijerph15071374
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Environmental Tobacco Smoke in Relation to Behavioral, Emotional, Social and Health Indicators of Slovak School Children

Abstract: Environmental tobacco smoke (ETS) exposure has been shown in general as a major environmental risk factor and deserves attention in vulnerable population groups. The aim of the project is to analyze the relationships among the ETS and behavior and health in 6−15-year-old children in Slovakia. The status of physical and mental health of children in relation to exposure to tobacco smoke was examined in a representative group of 1478 school children. The methods used, included anonymous questionnaires filled in b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
2
4
0
1
Order By: Relevance
“…In partial contrast with the results related to nationality, we found a significant influence of the educational level on the smoking dependence: lower maternal or paternal educational level were significant predictors of ETS exposure. This is in line with the results of previous studies performed in Italy [18] and in other countries [33,34,35,36], and it highlights the needs for specific smoking cessation interventions performed on smokers with a low educational level. These results were also confirmed by multivariate analyses, revealing that the lower education of the father or mother significantly increased the risk of children being exposed to ETS.…”
Section: Discussionsupporting
confidence: 91%
“…In partial contrast with the results related to nationality, we found a significant influence of the educational level on the smoking dependence: lower maternal or paternal educational level were significant predictors of ETS exposure. This is in line with the results of previous studies performed in Italy [18] and in other countries [33,34,35,36], and it highlights the needs for specific smoking cessation interventions performed on smokers with a low educational level. These results were also confirmed by multivariate analyses, revealing that the lower education of the father or mother significantly increased the risk of children being exposed to ETS.…”
Section: Discussionsupporting
confidence: 91%
“…The TSE group was at increased odds of having infectious diagnostic tests, laboratory tests, and radiologic tests obtained. These findings align with prior studies that indicate a relationship between TSE and respiratory-related outcomes including wheeze symptoms, decreased lung function ( 18 , 27 ), and an overall higher frequency of respiratory-related diseases ( 28 , 29 ). The present study’s findings underscore the need to adhere to the American Academy of Pediatrics’ recommendations for PED/UC healthcare professionals to universally screen for TSE in children, and provide cessation counseling to parental smokers to help them quit ( 4 ).…”
Section: Discussionsupporting
confidence: 91%
“…These results are in line with previous studies showed that low educational level of 1 or both parents were associated with ETS exposure in children 20,31,32 and infants from low-income or low-socioeconomic status families were most likely to be exposed to ETS. [31][32][33] Until now, there has no been a cutoff value for distinguishing between the exposed and unexposed ETS in infants. Other studies demonstrated hair nicotine values in infants but not included cutoff point.…”
Section: Discussionmentioning
confidence: 99%